Integrated Card Learning Media with Augmented Reality Based on Android for Elementary School Learning - Nurhikmah, A. Fatimah; Krismanto, Wawan; Mukhlisa, Nurul; Halik, Abdul; Faisal, Muh. (LPPM Undiksha, 2024)
Science learning in elementary schools should encourage students to explore, investigate and understand their environment, but this is hampered by the lack of media support that facilitates this. Departing from the need for innovation in learning methods in the current digital era. In elementary school, many students experience difficulty in understanding abstract concepts conveyed through conventional learning methods, which are generally textual and static visuals. Traditional approaches are often less attractive to students who have grown up in environments familiar with advanced technology. This research aims to create learning media products for elementary schools using Augmented Reality (AR) to facilitate ideal science learning. This research and development uses the Borg and Gall model. Research participants were fourth grade students in three elementary schools and their teachers. Data collection through observation, interviews and tests. Data was analyzed descriptively to describe quantitative and qualitative data. The research succeeded in developing a learning media product for elementary schools based on Augmented Reality (AR) called Media Karotena. The main results of the research show that the media is included in the appropriate category and is suitable for students and teachers. This development product has implications for the transformation of technology-based science learning. The implications of this research are The use of AR technology in learning can increase student engagement. By combining interactive visual media, students are more interested and motivated to learn, so that learning becomes more fun and effective.